Unidirectional barbed suture for vaginal cuff closure without backward stitch in total laparoscopic hysterectomy. Issue 9 (18th July 2018) - Misirlioglu, Selim; Boza, Aysen; Arslan, Tonguc; Urman, Bulent; Taskiran, Cagatay
Abstract: Aim: To evaluate the safety and efficacy of unidirectional barbed suture technique for vaginal cuff closure in total laparoscopic hysterectomy (TLH). Methods: In a retrospective chart review, data were analyzed from 165 patients who underwent a TLH with an unidirectional barbed suture technique for vaginal cuff closure from January 2012 to June 2016 at tertiary‐care university‐based teaching hospital and academic affiliated hospital. Vaginal cuff was closed by single layer 3/0 V‐Loc unidirectional 9″, 180 day Absorbable Wound Closure Device (Covidien Healthcare, Mansfield, MA) and the suture was not stitched backward to secure distal end. Results: A total of 165 patients were included and the median age was 50 years (range, 35–84 years). The median completion time for hysterectomy time was 100 min (range, 40–240 min) and the median vaginal cuff closure time was 7 min (range, 4–15 min). The median estimated blood loss was 87.8 mL (range 30–250 mL) and the median uterine weight was 200 g (range, 40–900 g). Intraoperative complication included bladder perforation (1.2%) and postoperative complications were vaginal cuff dehiscence (1.8%), cuff cellulitis (0.6%), vesicovaginal fistula (0.6%) and unexplained fever (0.6%). Conclusion: According to the results of current study, the use of unidirectional barbed suture without backward stitching appears to be safe for the vaginal cuff closure in TLH.